2013
DOI: 10.1016/j.celrep.2013.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Adult Neurogenesis in Drosophila

Abstract: Adult neurogenesis has been linked to several cognitive functions and neurological disorders. Description of adult neurogenesis in a model organism like Drosophila could facilitate the genetic study of normal and abnormal neurogenesis in the adult brain. So far, formation of new neurons has not been detected in adult fly brains and hence has been thought to be absent in Drosophila. Here, we used an improved lineage-labeling method to show that, surprisingly, adult neurogenesis occurs in the medulla cortex of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(156 citation statements)
references
References 39 publications
5
150
0
1
Order By: Relevance
“…Although the identity of concerned cell types is still unclear, this coincides with the detection of markers for local cell death in proliferation zones and the cell body cortex (Hofbauer & Campos-Ortega, 1990;Togane et al, 2012). While NBs generally stop dividing during early pupal development, a recent study using a modified lineagelabeling method unexpectedly provided evidence for continued neurogenesis in the adult medulla, albeit at low levels (Fernandez-Hernandez et al, 2013). Indeed, a small number of scattered cells in the medulla cortex could constitute quiescent NBs based on their expression of cytoplasmic Dpn and the ability to proliferate in response to injury.…”
Section: Terminating Neurogenic Divisionsmentioning
confidence: 71%
“…Although the identity of concerned cell types is still unclear, this coincides with the detection of markers for local cell death in proliferation zones and the cell body cortex (Hofbauer & Campos-Ortega, 1990;Togane et al, 2012). While NBs generally stop dividing during early pupal development, a recent study using a modified lineagelabeling method unexpectedly provided evidence for continued neurogenesis in the adult medulla, albeit at low levels (Fernandez-Hernandez et al, 2013). Indeed, a small number of scattered cells in the medulla cortex could constitute quiescent NBs based on their expression of cytoplasmic Dpn and the ability to proliferate in response to injury.…”
Section: Terminating Neurogenic Divisionsmentioning
confidence: 71%
“…This finding suggests that flower participates in the recognition and elimination of misconnected neurons. Similarly, a recent study [42] showed that flower is required for efficient elimination and replacement of old neurons by newly generated neurons during regeneration in the adult Drosophila brain after mechanical injury [42,43]. These two studies connect for the first time the mechanisms involved in cell competition with the elimination of neurons during development and regeneration.…”
Section: Cell Competition In Growing Tissues Adults and Neuronsmentioning
confidence: 88%
“…The possibility of adult neural regeneration in the brain of dCORL mutants leads to the essentially unexplored area of adult brain neuroblast division in Drosophila. A Flybase search identified only a single paper describing the activation of adult brain neuroblast cell division in response to acute damage (Fernández-Hernández et al 2013). In contrast there is widespread interest in understanding the origins of adult born neurons in the mammalian brain ( e.g.…”
Section: Discussionmentioning
confidence: 99%